Pengaruh Pendidikan Hukum Syariah terhadap Validitas Akad Ijarah di Bank Syariah: Studi Kasus di Indonesia - Muhammad Syukron (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2022)
This study examines the influence of Islamic law education on the validity of ijarah contracts in Islamic banks, focusing on the conditions in Indonesia. The research investigates how Islamic law education affects bank staff's understanding of the Sharia principles underlying ijarah contracts and its impact on achieving more valid implementations in accordance with Sharia provisions. The research employs a qualitative approach with a case study methodology, involving in-depth interviews and document analysis. Findings indicate that Islamic law education plays a crucial role in enhancing awareness and understanding among bank staff, thereby making a significant contribution to the development of the Islamic financial market in Indonesia. This research highlights the crucial role of Islamic law education in enhancing the validity of ijarah contracts in Islamic banks. By focusing on the influence of this education and factors affecting compliance with Sharia principles, the study provides insights into steps banks can take to improve implementation and adherence to Sharia principles. Islamic law education plays a pivotal role in deepening bank staff's understanding of the Sharia principles underpinning ijarah contracts, enabling more valid implementations in accordance with principles that prohibit riba, gharar, and maysir. Factors such as structured education and training, awareness of compliance importance, and management support in fostering a culture of compliance significantly influence the level of compliance among bank staff with Sharia principles. Keywords : Islamic Law Education, Validity of Ijarah Contracts, Sharia Compliance, Islamic Banks, Development of Islamic Financial Markets